Analysis of the Quality of the Registration Services of Haji Travelers in the Office of the Ministry of Religion, Bengkulu City - Aldi Syafitra Anwari; Sulisti Apriani; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to analyze the quality of service for the registration of pilgrims at the Office of the Ministry of Religion of the City of Bengkulu, Permenpan RB Number 14 of 2017. The sampling method was used by simple random sampling with a sample size of 100 pilgrims who registered for the pilgrimage. The method of analysis in this research is qualitative and quantitative analysis based on Permenpan RB Number 14 of 2017. The results of the study show that the quality of the Hajj pilgrims 'registration service in the PHU Section of the Office of the Ministry of Religion of Bengkulu City with the criteria of "Good" is indicated by the average value of the respondents' perceptions of 3.3011 in the interval 3.0644-3.532. The value of the Community Satisfaction Survey (SKM) was 3.2681 in the interval 3.0644-3.532, as well as the value of SKM after conversion of 81.7025 in the interval 76.61-88.30 with the criteria "Good (B)". Among the 9 indicators of service quality, the highest value is in the first indicator, namely costs/tariffs with an average value of 4.00 in the 3.5324-4.00 interval and SKM after being converted at 100.00 is at the interval of 88.31-100,000 with the criteria "Very Good (A)". While the lowest average value on the indicator for handling complaints complaints with an average value of 2.94 is in the 2.60-3.064 interval and SKM after being converted is 73.50 in the interval 65.00-76.60 with the criteria "Not Good. (C) ".